Building a Model of Organizational Activities Experience in Natural Sciences under Stem Education Orientation (Global Journal of Human-Social Science, 2023)
STEM educational-oriented Natural Science experience activities are learner-oriented activities Taking learners as the center in all natural science research activities applying engineering technology and mathematics STEM in solving practical problems Based on theoretical research on experiential activities STEM education and the characteristics of Natural Sciences the article studies the educational forces inside and outside the school From there it is proposed to build a model of organizational structure for experiential activities in Natural Sciences oriented toward STEM education The results of this research are meaningful in helping principals see the importance and significance of coordinating educational forces inside and outside the school in organizing experiential activities in Natural Sciences according to orientation STEM education for students
Keywords: model; organization; activities; experience; natural sciences; stem education